Addition of Fibroblast-Stromal Cell Markers to Immune Synovium Pathotypes Better Predicts Radiographic Progression at 1 Year in Active Rheumatoid Arthritis - Zhang, Xue-Pei; Ma, Jian-Da; Mo, Ying-Qian; Jing, Jun; Zheng, Dong-Hui; Chen, Le-Feng; Wu, Tao; Chen, Chu-Tao; Zhang, Qian; Zou, Yao-Yao; Lin, Jian-Zi; Xu, Yan-Hui; et al. (Frontiers in Immunology, 2021)
Objectives: To investigate if addition of fibroblast-stromal cell markers to a classification of synovial pathotypes improves their predictive value on clinical outcomes in rheumatoid arthritis (RA). Methods: Active RA patients with a knee needle synovial biopsy at baseline and finished one-year follow-up were recruited from a real-world prospective cohort. Positive staining for CD20, CD38, CD3, CD68, CD31 and CD90 were scored semi-quantitatively (0-4). The primary outcome was radiographic progression defined as a minimum increase of 0.5 units of the modified total Sharp score from baseline to one year. Results: Among 150 recruited RA patients, 123 (82%) had qualified synovial tissue. Higher scores of CD20+ B cells, sublining CD68+ macrophages, CD31+ endothelial cells and CD90+ fibroblasts were associated with less decrease in disease activity and greater increase in radiographic progression. A new fibroblast-based classification of synovial pathotypes giving more priority to myeloid and stromal cells classified samples as myeloid-stromal (57.7%, 71/123), lymphoid (31.7%, 39/123), and pauci-cellular pathotypes (10.6%, 13/123). RA patients with myeloid-stromal pathotype showed the highest rate of radiographic progression (43.7% vs. 23.1% vs. 7.7%, P=0.011), together with the lowest rate of Boolean remission at 3, 6, 12 months. Baseline synovial myeloid-stromal pathotype independently predicted radiographic progression at one year (adjusted OR: 3.199, 95% confidence interval [95% CI]: 1.278, 8.010). Similar results were obtained in a subgroup analysis of treatment-naive RA. Conclusions: This novel fibroblast-based myeloid-stromal pathotype could predict radiographic progression at one year in active RA patients which may contribute to the shift of therapeutic decision in RA.